Pengolahan Tanaman Tebu Sebagai Pembuatan Gula Merah Di Desa Buter Balik, Kecamatan Kute Panang, Kabupaten Aceh Tengah - Agung Rida Ilahi; Cut Julita; Lili Rahmayanti; Fatimah Fatimah; Sofi Imamah Banurea; Mahmud Basuki (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
Buter Balik Village, Kute Panang District, located in Central Aceh District, has fertile land and the majority of the people are farmers. Buter Balik Village has several community livelihoods, including coffee, chili, avocado, sugarcane, and so on. Most of the people in the village have sugarcane plantations on average. The community cultivates their own sugarcane plantations without depending on other people or outside the area. The community also processes the sugarcane plants themselves into processed products in the form of brown sugar. The method used in this article is descriptive qualitative. The purpose of this observation is to find out the process of making brown sugar from sugarcane in Buter Balik Village. The results of the observations have concluded that brown sugar from sugar cane juice has several benefits including preventing fatigue, meeting the body's mineral needs, maintaining bone health, and there are many benefits to be gained from brown sugar.